Educación militar e universidad en Argentina atual - Soprano, Germán (2013)
Argentinian officials'reformation process has required the revision of the concepts of the relationship between "military education" and "university education". For some high officials, there is a complementarity between the two kinds of education; others think that higher education is a necessary deviation from soldier training; while, for a third group, there is incompatibility.
O processo de reforma da formação básica dos oficiais na Argentina tem exigido uma revisão das concepções sobre as relações entre "educação militar" e "educação universitária". O artigo analisa essas concepções nos oficiais superiores com responsabilidade na área de educativa, achando alguns que acreditam na complementaridade, outros que acham a educação universitária um desvio necessário no treinamento do soldado, e outros uma incompatibilidade.
Keywords: Military education; University; Officials; Argentina; Educação militar^lpt; Universidade; Oficiais